1994
DOI: 10.1007/bf02020161
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound diagnosis of thymic hemorrhage in an infant with late-onset hemorrhagic disease

Abstract: Thymic hemorrhage related to coagulopathy by vitamin K deficiency is a rare condition. We report a case in a 4-week-old boy presenting with acute onset of respiratory distress and anemia. Ultrasound examination of a compressive anterior mediastinal mass established the diagnosis of thymic hemorrhage and allowed us to follow resolution under medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Imaging findings in the nine cases of SHNT in perinatal and infantile period [3][4][5][6][7][8][9], this report included, are summarized in Table 1-2. Four of them were presented in a very early neonatal period and the other five cases were presented in an early infantile period (between the age of 4 weeks and 4 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging findings in the nine cases of SHNT in perinatal and infantile period [3][4][5][6][7][8][9], this report included, are summarized in Table 1-2. Four of them were presented in a very early neonatal period and the other five cases were presented in an early infantile period (between the age of 4 weeks and 4 months).…”
Section: Discussionmentioning
confidence: 99%
“…The management of an infantile thymic hemorrhage usually started with normalization of coagulation indices by giving vitamin K and fresh frozen plasma, and adding packed red cell to the anemic ones [3][4][5][6][7][8][9]. The coagulopathy was usually corrected within 6-24 hours.…”
mentioning
confidence: 99%
“…Then 2 cases of spontaneous thymic haemorrhage with positive outcome after surgery are described in 1974 by Woolley et al [ 10 ]. Several years after Urvoas et al [ 7 ] presented a case of spontaneous thymic haemorrhage in a 4-week-old boy, with good resolution after medical treatment. In the case reported by Walsh et al [ 9 ] in 1996, the newborn showed severe neonatal respiratory distress, which led to death at a few hours of age.…”
Section: Discussionmentioning
confidence: 99%
“…A Medline search revealed 6 case reports. 1,2,[6][7][8][9] Two of the cases presented immediately after delivery and were caused by early onset VKDB. 7,8 Both received IM vitamin K prophylaxis.…”
Section: Commentarymentioning
confidence: 99%
“…Two other cases, as in ours, were caused by late-onset VKDB. 1,2 One received "the usual prophylactic dose of vitamin K1." He was a premature infant born at 36 weeks gestation and weight 2200 g at birth.…”
Section: Commentarymentioning
confidence: 99%